PENGARUH KONSENTRASI ASAM NITRAT SEBAGAI REAGEN DEKALSIFIKASI TERHADAP KUALITAS PEWARNAAN SAFRANIN O PADA TULANG - Yusdarfadri, Rita Permatasari; Verdian Putra, Fuji (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
In histotechnology, bones play a certain role in the diagnosis of disease. The dilemma experienced by an anatomical pathology laboratory technician in making bone preparations or preparations containing high calcium salts. To overcome the hardness of the tissue due to the presence of calcium salts, a special technique called decalcification is needed. Strong acids such as hydrochloric or nitric acid are the fastest decalcification solutions in the decalcification process. Safranin is a cationic dye used in histology and cytology to differentiate and identify various tissues and cells. This study aims to determine the effect of nitric acid concentration as a decalcification reagent on the quality of safranin O staining in bones. This study uses an experimental method. The samples used in this study were beef ribs, then the specimens were decalcified with 5%, 10% and 15% nitric acid. The results showed that the nitric acid decalcification agent at concentrations of 5% and 10% obtained a consistency result of 1, meaning that the consistency of the beef rib bone sample was not soft, while 15% Nitric Acid obtained a consistency result of 3, meaning that the consistency of the beef rib bone sample was soft. Then, in the histological assessment of bone tissue preparations that have been stained with Safranin O, it was obtained at a concentration of 5% staining intensity with a final score grade of 0, meaning poor quality. At a concentration of 10% staining intensity with a final score of 1, meaning poor quality, and histological assessment of a concentration of 15% staining intensity with a final score of 2, meaning good quality. From this study, it can be concluded that the results of safranin O staining on beef ribs show differences in staining quality at different concentrations of decalsifying agents.